Automatic XML Extraction from Word and Formatting of E-Book Formats: Insight into the Open Source Academic Publishing Suite (OS-APS) - Borchert, Carsten; Cozatl, Roberto; Eichler, Frederik; Hoffmann, Astrid; Putnings, Markus (Publications, 2022)
Due to resource constraints, most Diamond Open Access journals publish fewer than 25 articles per year, and 75% of journals are not able to provide their content in XML and HTML, primarily providing only PDFs. In order to keep up with larger commercial publishers, a high degree of automation and streamlining of processes is necessary. The Open Source Academic Publishing Suite (OS-APS) project, funded by the German Federal Ministry of Education and Research, aims to achieve this. OS-APS automatically extracts the underlying XML from Word manuscripts and offers optimization and export options in various formats (PDF, HTML, EPUB). The professional corporate design, e.g., of the PDFs, is managed automatically using templates or creating one’s own using a Template Development Kit. OS-APS will also connect to scholarly-led and community-driven publishing platforms such as Open Journal Systems (OJS), Open Monograph Press (OMP), and DSpace: the software will be able to be integrated into a wide range of publication processes, whether at small, low-resource commercial Open Access Publishers, or institutional and Diamond Open Access Publishers.
CRIS-Team Scopus Importer:2023-04-07
Keywords: automatic typesetting; media-neutral publishing; open access; open source; scholarly publishing; XML/HTML conversion